Li dynamics in amorphous LiNbO 3 as probed by solid state NMR on different length scales - Wilkening, Martin; Masoud, Muayad; Heitjans, Paul (Diffusion Fundamentals, 2008)
Long-range Li diffusion parameters of amorphous LiNbO3 are probed by 7Li two-time spin-alignment echo NMR spectroscopy which is sensitive to slow Li dynamics. The jump rates which were extracted from the spin-alignment echo decay curves exhibit Arrhenius behaviour between 293 K and 413 K. The activation energy (0.41(1)eV) is in good agreement with that of the high-temperature flank of the 7Li NMR spinlattice relaxation rate peak. The latter was predicted to be about 0.4 eV when taking into account the frequency dependence of the corresponding spin-lattice relaxation rates on the low-T flank (see Wilkening et al., Phys. Chem. Chem. Phys. 4 (2002) 3246). Previous measurements of the spin-lattice relaxation rate had to be restricted to temperatures below 450 K in order to avoid crystallization of the material. Thus, only the low-temperature flank of the diffusion induced spin-lattice relaxation rate peak had been accessible yielding information about short-range Li diffusion.